Hubungan Ukuran Antropometri terhadap Perkembangan Anak Usia 3-24 Bulan di Desa Mudung Darat - Hia, Nia Agustina; Rahmawati, Diane; Rahmawati, Dwi; Astria, Niki (Jurnal Akademika Baiturrahim Jambi, 2024)
In the growth and development of children, there are events that they experience, namely periods of acceleration and deceleration. This period will be different in one organ of the body. Acceleration and deceleration are different events in each organ of the body but are still interconnected with each other. Anthropometric measurements are measurements used to determine a person's nutritional state. In order to obtain the right results, a benchmark is given as a guide. Measurement of physical size in babies/children consisting of: BB, TB and Anthropometric Circumference (LIKA, LIDA, LILA and LIPER). This research design is quantitative research with a cross sectional approach with the Mann-Whitney statistical test. The population in this study was all children aged 3-24 months who visited the Posyandu in Mudung Darat Village, totaling 84 children. The sample in this study was all toddlers aged 3-24 months who visited the Posyandu in Mudung Darat Village, totaling 46 children. Samples were selected using purposive sampling technique. Data collection techniques use observation sheets and Developmental Pre-Screening Questionnaire (KPSP). Bivariate analysis shows that the relationship between anthropometric measurements and child development is obtained by p-value = 0.031, meaning <0.05, so the hypothesis (H0) and the alternative hypothesis (H1) can be stated as accepted. There is a significant relationship between anthropometric measurements and the development of children aged 3-24 months at the Mudung Darat Village Posyandu studied with a p-value of 0.031.